Towards trustworthy cloud service selection: monitoring and assessing data privacy - Basso, Tania; Silva, Hebert de Oliveira; Montecchi, Leonardo; de França, Breno Bernard Nicolau; Moraes, Regina Lúcia de Oliveira (Anais do Workshop de Testes e Tolerância a Falhas (WTF), 2019)
Cloud services consumers deal with a major challenge in selecting services from several providers. Facilitating these choices has become critical, and an important factor is the service trustworthiness. To be trusted by users, cloud providers should explicitly communicate their capabilities to ensure important functional and non-functional requirements (such as security, privacy, dependability, fairness, among others). Thus, models and mechanisms are required to provide indicators that can be used to support clients on choosing high quality services. This paper presents a solution to support privacy measurement and analysis, which can help the computation of trustworthiness scores. The solution is composed of a reference model for trustworthiness, a privacy model instance, and a privacy monitoring and assessment component. Finally, we provide an implementation capable of monitoring privacy-related information and performing analysis based on privacy scores for eight different datasets.